Various Financial Applications of Regime-Switching Jump-Diffusion Models - Yang, Yu (Curtin University, 2020)
The regime-switching jump-diffusion models have attracted great attention from the research community recently due to their ability to capture the random market movements during both short-term and long-term periods. This research focuses on the applications of various regime-switching jump-diffusion models to two important financial problems, the mean-variance asset-liability management problem and the pricing of variance (volatility) swaps, where little work has been done to our knowledge.